Low lamin A expression in lung adenocarcinoma cells from pleural effusions is a pejorative factor associated with high number of metastatic sites and poor Performance status. - Elise Kaspi; Diane Frankel; Julien Guinde; Sophie Perrin; Sophie Laroumagne; Andrée Robaglia-Schlupp; Kevin Ostacolo; Karim Harhouri; Rachid Tazi-Mezalek; Joelle Micallef; Hervé Dutau; Pascale Tomasini; et al. (PLoS ONE)
The type V intermediate filament lamins are the principal components of the nuclear matrix, including the nuclear lamina. Lamins are divided into A-type and B-type, which are encoded by three genes, LMNA, LMNB1, and LMNB2. The alternative splicing of LMNA produces two major A-type lamins, lamin A and lamin C. Previous studies have suggested that lamins are involved in cancer development and progression. A-type lamins have been proposed as biomarkers for cancer diagnosis, prognosis, and/or follow-up. The aim of the present study was to investigate lamins in cancer cells from metastatic pleural effusions using immunofluorescence, western blotting, and flow cytometry. In a sub-group of lung adenocarcinomas, we found reduced expression of lamin A but not of lamin C. The reduction in lamin A expression was correlated with the loss of epithelial membrane antigen (EMA)/MUC-1, an epithelial marker that is involved in the epithelial to mesenchymal transition (EMT). Finally, the lamin A expression was inversely correlated with the number of metastatic sites and the WHO Performance status, and association of pleural, bone and lung metastatic localizations was more frequent when lamin A expression was reduced. In conclusion, low lamin A but not lamin C expression in pleural metastatic cells could represent a major actor in the development of metastasis, associated with EMT and could account for a pejorative factor correlated with a poor Performance status.